Impression Cytology and In Vivo Confocal Microscopy of Lip Mucosa Compared With Labial Gland Biopsy and Classification Criteria In Patients With Clinically Suspected Primary Sjögren’s Syndrome - Hao, Ran; Liu, Ziyuan; Chou, Yilin; Wang, Yuexin; Ren, Xiaotong; Jiang, Xiaodan; Li, Xuemin (Frontiers in Immunology, 2022)
Purpose The study assessed the validity of impression cytology (IC) and in vivo confocal microscopy (IVCM) of lip mucosa compared with labial gland biopsy, anti-Sjögren’s syndrome A (SSA)/Ro antibody status, and classification criteria in suspected primary Sjögren’s syndrome (pSS) patients. Methods Clinically suspected pSS patients (n = 201) were enrolled consecutively and were divided into pSS (n = 56) and control (n = 145, only with dryness) groups according to the American College of Rheumatology-European League Against Rheumatism (ACR-EULAR) criteria. All patients underwent lip mucosa IC (inflammatory cell density) and IVCM (epithelium/intrinsic layer thickness and labial gland density/diameter) analyses. The associations between IC/IVCM parameters and clinical/laboratory results were analyzed. Results The absolute agreement between positive lip mucosal IC (≥50 cells/4 mm2) and the ACR-EULAR criteria (94.5%)/labial gland biopsy (95.5%) was good, with sensitivities of 82.1 and 85.2%, respectively, and a specificity of 99.3%. Compared with controls, IVCM revealed significant lip mucosal atrophy and glandular decreases in the pSS group (all P = 0.000). The sensitivities for diagnosing pSS corresponding to a lamina propria thickness ≤128 μm and a gland diameter ≤114 μm were 85.7 and 89.3%; the specificities were 90.3 and 95.9%, respectively. A combination of positive IC/IVCM and anti-SSA/Ro antibody results showed a high predictive value for diagnosing pSS. Conclusions IC and IVCM could detect distinctive cellular and morphological changes in the lip mucosa of patients with pSS. These noninvasive and easy-to-perform examinations may be an alternative to labial gland biopsy for diagnosing pSS.